Synthesis of ceramic pigments from industrial wastes: Red mud and electroplating sludge. (October 2018) - Carneiro, J.; Tobaldi, D.M.; Capela, M.N.; Novais, R.M.; Seabra, M.P.; Labrincha, J.A.
Highlights: Red mud and electroplating sludge combined to prepare ceramic pigments. Dark pigments with structure based on a chrome-iron-nickel spinel. Waste-based pigments display good color stability in ceramic glazes. Stability/tinting strength of waste-based pigments competitive with commercial ones. Abstract: The perception of industrial waste has changed, in the last decades, from an economic and environmental problem to a potential raw material. In this work, the synthesis of a stable pigment was prepared by combining two hazardous and unexplored wastes: red mud (RM, rich in Fe) and electroplating sludge (ES, rich in Ni/Cr). The wastes were mixed in different proportions and calcined at 1200 °C. Black and brown pigments were obtained from the mixture of RM/ES in 1:3 and 1:1 wt proportions, respectively. The color was given by the chrome-iron-nickel spinels, based on Ni 2+ 3 T1g ( 3 F) transitions (≈13, 000 cm −1 ), Cr 3+ 4 A2g  →  4 T1g ( 4 F) transitions (≈24, 400 cm −1 ) and Fe 3+ (≈15, 000–≈22, 500 cm −1 ). The achieved coloring strength and thermal stability on various ceramic glazes render excellent prospects for the industrial application of such waste-based pigments.